Comprehensive Review Article on Nutraceuticals and Herbal Medicines - Anil Viljya Pawara; Mrunal p.Pendharkar; Neha P.Patil; Krutadhya P. Patil; Sunil P. Pawar (International Journal of Nutritions, 2026)
Ayurveda is a roughly 5000-year-old medical system that is mainly practiced in India. It emphasizes the body, mind, and spirit in illness prevention and treatment and incorporates herbal treatments and diet. Ayurveda is one of the traditional medical systems in India. Ayurveda is based on the idea of avoiding needless pain and leading a long, healthy life. Ayurveda employs natural remedies to eradicate the disease's underlying cause by reestablishing equilibrium while simultaneously fostering a healthy lifestyle to stop imbalance from happening again. Polyherbal formulations are those that contain two or more herbs. Nutraceuticals are essential food components with both medicinal and nutritional qualities. Active ingredients such as dietary fibers, collagen hydrolysate, and carotenoids aid in the healing process. Herbal and nutraceutical formulations are the most well-known worldwide. There are less adverse effects with hal formulations. Herbal formulations have gained popularity in recent years. Nowadays, more people prefer herbal remedies. Plant extracted powders are usually used as supplements because they are rich in minerals, vitamins, and other nutrients. Herbal extracts are usually used as powders and capsules, but formulators find it challenging to formulate these products due to their high dosage, harsh taste, very poor flowability, and low compressibility.
Keywords: Dietary supplements; Probiotics; Therapeutic Properties; and functional foods; disease prevention; prebiotics